Analysis of the heart rate variability in individuals submitted to CV4 maneuver. - Santos LS; Coutinho EB; do Bonfim RVF (Revista Terapia Manual)
Introdution[sic]: Craniosacral therapy is fundamentally based on the existence of a tactful rhythm originated from the mobility existent among cranial bones. The technique of the fourth ventricle compression (CV-4) reduces, through a light compression, this cranial mobility through an occipital plaque, increasing the hydraulic pressure of the intracranial fluid, redirecting the fluid throughtout[sic] other available ways. The use of the technique affects the activity of the diaphragm and the autonomous control of respiration, and seems to relax the tonus of the sympathetic nervous system in significative degree, besides it improves the linphatic circulation by the body. Objective: The present study aims to analyze the heart rate variability in individuals submitted to CV-4 manuever. Method: The research was performed in 14 clinically healthy individuals, aging 18 to 30 years old. These individuals passed through an evaluation, which corresponded to a questionnaire and a physical exam, and were monitored with the Polar S810i and submitted to the experiment. The electrocardiographic signals were transferred to a computer equipped with the Polar Precision Performance Software exported in text files and filtered with Microsoft Excel. The analysis of heart rate variability was calculated through the continuous transformed Wavelet on Matlab platform 6.1. The obtained data were submitted to D'Agostino Normality Test and were compared using Student's t-test with level of significance of 5% (p < 0,05). Results: The discovered results turned evident the predominance of parasympathetic nervous activity in all phases of the study. Between the phases of relax and performance of the technique, it was observed a significative decrease in spectral potention in the band of low frequence (LF) with significative increase after the withdraw of the stimulus. The analysis of the reasons of spectral bands of low and high frequence (LF/HF) shows a significative reduction in the relax phase for the technique and a significative increase in the technique for recovery. Conclusion: The results of this study in experimental conditions used permitted to suggest that the use of CV-4 maneuver provokes a decrease in sympathetic activity increasing the heart rate variability of the individuals studied.